Microcystin-LR induced transgenerational effects of thyroid disruption in zebraﬁsh offspring by endoplasmic reticulum stress-mediated thyroglobulin accumulation and apoptosis. (1st April 2023) - Si, Weirong; Zhao, Mengjie; Che, Huimin; Wu, Zaiwei; Xiao, Yuchun; Xie, Xinxin; Duan, Jiayao; Shen, Tong; Xu, Dexiang; Zhao, Sujuan
Abstract: MC-LR can interfere with thyroid function in ﬁsh, but the underlying mechanism is still unclear. Current study focuses to study the intergenerational inheritance of MC-LR-induced thyroid toxicity in zebrafish and in rat thyroid cells. In vivo experiments, adult female zebrafish (F0) were exposed to MC-LR (0, 5, and 25 μg/L) for 90 days and mated with male zebrafish without MC-LR exposure to generate F1 generation. F1 embryos were allowed to develop normally to 7 days post-fertilization (dpf) in clear water. In the F0 generation, MC-LR induced disturbance of the hypothalamic-pituitary-thyroid (HPT) axis, leading to a decrease in the production of thyroid hormones. Maternal MC-LR exposure also induced growth inhibition by altering thyroid hormones (THs) homeostasis and interfering with thyroid metabolism and development in F1 offspring. Mechanistically, MC-LR caused excessive accumulation of ROS and induced ER stress that further lead to activation of UPR in the F0 and F1 offspring of zebrafish. Interestingly, our ﬁndings suggested that MC-LR exposure hampered thyroglobulin turnover by triggering IRE1 and PERK pathway in zebrafish and FRTL-5 thyroid cells, thus disturbing the thyroid endocrine system and contributing to the thyroid toxicity from maternal to its F1 offspring of zebrafish. Particularly, inhibition of the IRE1 pathway by siRNA could alleviate thyroid development injury induced by MC-LR in FRTL-5 cells. In addition, MC-LR induced thyroid cell apoptosis by triggering ER stress. Taken together, our results demonstrated that maternal MC-LR exposure causes thyroid endocrine disruption by ER stress contributing to transgenerational effects in zebraﬁsh offspring. Graphical abstract: Image 1 Highlights: Maternal MC-LR exposure induced growth inhibition in F1 generation. Thyroid toxicity from maternal to its F1 offspring were observed after MC-LR exposure. ER stress induced apoptosis in thyroid cells after MC-LR treatment. MC-LR exposure hampered thyroglobulin turnover by triggering IRE1 and PERK pathway. Inhibition of the IRE1 pathway could alleviate thyroid development injury induced by MC-LR.